Deteksi Kadar Alkohol Menggunakan Sensor MQ3 Berbasis Website - Munaf Ismail; Arief Marwanto; Muhamad Haddin (Infotekmesin, 2021)
According to the Head of the Indonesian National Police (Kapolri) General Idham Azis, the number of deaths from accidents that occurred in 2019 reached 23,530. A total of 40% of the deaths from traffic accidents are caused by human error and the influence of alcohol. The high number of deaths from traffic accidents due to the influence of alcohol is a concern for all of us. Excessive alcohol consumption is dangerous when driving because consuming alcohol will affect a person's temperament and worsen driving behavior by reducing awareness, leading to accidents. A system that is able to detect the alcohol level of a vehicle driver that can be monitored anywhere is needed, as information to alert motorists to the influence of alcohol in order to prevent traffic accidents online and on a web-based basis. Using the MQ-3 sensor for alcohol detection and the ESP8266 processor in WeMos WiFi.  The average percentage error in the measurement of the measured sample was found to have an error value of: 3.6%. Research has also succeeded in reading alcohol levels through websites.